Symbiotic Response of Field Grown Soybean Varieties to Rhizobia Inoculant in Western Ethiopia - Gebrehana, Zerihun Getachew; Misgana, Mathewos; Anbessa, Bakala (European Journal of Applied Sciences, 2024)
Rhizobium inoculation is a widely adopted practice for legume crops like soybeans, facilitating the formation of N2-fixing symbiotic associations. Effective rhizobia strains have been used as rhizobial inoculants to maximize nitrogen fixation, resulting in adequate yields. However, the effectiveness of these inoculants varies depending on soybean varieties, with beneficial effects observed on nodulation and grain yield. A study evaluated the potential of elite Rhizobial strains (Mar-1495, SB-12, and SB-14) on soybean nodulation, growth, and seed yield across different soybean varieties (Gishema, Wello, and Belessa-95) under farmer field conditions in different cropping seasons. The combined ANOVA results showed no significant interaction between soybean variety and Rhizobia inoculant on growth and yield. However, there was a notable influence of the year on all parameters measured, reported for each experimental season. Rhizobial inoculation notably improved root nodulation, growth, and seed yield in soybean varieties. Mar-1495 demonstrated a substantial increase in growth and yield, with a 44.6% yield increment compared to the control. On the other hand, SB-12 exhibited poorer performance. Variation in response to Rhizobium inoculation was observed between locations, likely due to soil fertility differences, mostly soil N and P. Overall, using compatible and effective rhizobial inoculants like MAR-1495 and SB-14 can enhance nodulation, growth, and seed yield, particularly in the Gishema and Belessa-95 soybean varieties.